Correlates of electroconvulsive therapy with neurocognitive functioning, subjective memory and depression - Brooke A. Schauder; Tamara A. Malcolm; Amanda Tan; Digant Dave; Alexander L. Peterkin; Katherine L. Taylor (Journal of Affective Disorders Reports, 2022)
Objective: The study purpose was to evaluate the impact of a series of electroconvulsive therapy treatments (ECT) on depression and neurocognitive functioning. Secondary objectives were to evaluate the relationships among depression, neurocognitive functioning and subjective memory post-treatment. Methods: Data from 44 participants was analyzed over the course of ECT. Montreal Cognitive Assessment (MoCA) scores were gathered pre-ECT, post-acute ECT, and 6-7 weeks subsequently. Montgomery-Asberg Depression Rating Scale (MADRS) data, Patient Health Questionnaire-9 (PHQ-9) data, and patient's subjective memory impairment ratings were gathered pre-ECT and post-acute ECT. Neither patients nor clinicians were blinded. Results: There was a significant decrease of 4.3 points over the acute series of ECT from the first to second MoCA with a p value of <0.001. There was a non-significant score increase of 0.26 after a period of recovery from the first to last MoCA. No significant relationship was found between patients’ perception of memory impairment and their cognitive score (as measured by MoCA) or their depression level (as measured by MADRS and PHQ-9). There was a significant decrease in clinician-rated depression as measured by MADRS over the course of ECT, with average decrease of 16.9 points (p <0.001). There was a significant decrease in self-rated depression as measured by PHQ-9 over the course of ECT, with an average decrease of 11.3 points (p <0.001). There was a significant decrease in the difficulty caused by these depressive symptoms as noted on the PHQ-9 at the last time point (p <0.001). Limitations: The primary limitation of this study was relatively small sample size. Conclusions: Neurocognitive functioning, as measured by MoCA, decreased during the acute phase and then recovered to pre-ECT levels after a limited period of time. Patients’ subjective rating of memory impairment was not correlated with depression scores on MADRS or PHQ nor with the MoCA score. ECT treatment correlated with decreased self-rated depression (PHQ-9) and clinician-rated depression (MADRS). Decrease in self-reported difficulty associated with depressive symptoms decreased significantly over the course of ECT.